100 Selected Stories - Henry, O., 1862-1910 (Ware Wordsworth Editions Ltd., 2012)
A collection of 100 of author''s finest stories; it describes life south of the Rio Grande and chronicles the activities and concerns of ''the four million'' ordinary citizens who inhabited turn-of-the-century New York
Keywords: Short stories, American